Client-friendly continuous-variable blind and verifiable quantum computing - Liu, Nana; Demarie, Tommaso F.; Tan, Si-Hui; Aolita, Leandro [UNESP]; Fitzsimons, Joseph F. (American Physical Society (APS), 2019)
We present a verifiable and blind protocol for assisted universal quantum computing on continuous-variable (CV) platforms. This protocol is experimentally friendly to the client, as it only requires Gaussian-operation capabilities from the latter. Moreover, the server does not require universal quantum-computational power either, its only function being to supply the client with copies of a single-mode non-Gaussian state. Universality is attained based on state injection of the server's non-Gaussian supplies. The protocol is automatically blind because the non-Gaussian resource requested to the server is always the same, regardless of the specific computation. Verification, in turn, is possible thanks to an efficient non-Gaussian state fidelity test where we assume identical state preparation by the server. It is based on Gaussian measurements by the client on the injected states, which is potentially interesting on its own. The division of quantum hardware between client and server assumed here is in agreement with the experimental constraints expected in realistic schemes for CV cloud quantum computing.